FormBuilder: framework for automatic generation of primefaces screens based on annotations (Revista Brasileira de Contabilidade e Gestão, 2013)
This article presents the framework FormBuilder, developed to automate the generation of screens PrimeFaces and expedite the development of Web applications. The framework generates three types of components: button, edit box and check box, that will be generated based on annotations declared in control classes developed by the user, the connection between the control class and the web page will be accomplished through a custom tag JSF. In the end of the article is displayed a example application that uses the framework developed.
Keywords: framework; screen generator; JSF; java; primefaces